Формула старый горoд Гeдиминa - Лавринец, Павел Михайлович (Kalbotyra, 1997)
Vilnius, the capital of Lithuania and the most prominent cultural center of different ethnic groups which live here, has been and still is in multinational poetry. The most famous periphrastic name for Vilnius is the old town of Gediminas. This name and its different variants are presented in different verses and poems written by Russian, Polish, Lithuanian, and Belarussian poets, despite the fact they belong to different political groups and have different ethical interpretations. It is the main form of the Vilnius text, which is supported by historical and local realities and is based on the mythological imaginations of the foundation of Vilnius. This form reflects the poetical interpretation of the Lithuanian capital and its history.